Study On The Template Protection Technique In Biometric Authentication System - Ong, Thian Song (2008)
Template protection is a relatively new research direction spurred by the need to resolve security and privacy risks associated with the storage of biometric user templates. Specifically, it can be classified into two main approaches, i.e. Cancelable Biometrics (CB) and Biometric Encryption (BE).